Dimensi Sosiologis Dalam Kebijakan Pembangunan Nagari di Sumatera Barat (Studi Kasus: Nagari Sungai Pua Kab. Agam) - Handrina, Emi (LPPM Universitas Dharma Andalas, 2025)
The purpose of this activity is to determine the Sociological Dimension in Village Development Policy in West Sumatra (case study: Sungai Pua Village, Agam Regency). The research method used is qualitative descriptive type. Data collection techniques used are such as: interviews, observations, and document/literature analysis. Interviews were conducted by preparing guidelines and equipment such as notes and stationery. The data analysis technique in this study used a qualitative approach based on Miles Huberman's theory which includes three stages: data collection, data reduction, and data presentation. The conclusion of the study is that the Village Medium-Term Development Plan (RPJM Nagari) in Sungai Pua Village, Agam Regency which is regulated in Agam Regency Regional Regulation Number 12 of 2007 is a comprehensive village development plan for the next five years, including budget policies and priority programs to be implemented. The RPJM Nagari is prepared to provide guidance in managing the potential and problems of the village for the village community and institutions at a higher level.